Boredom, art, and activism: notes on the experiences of people with disabilities in Mexico during the COVID-19 pandemic - Beatriz Miranda-Galarza; Benjamín Mayer-Foulkes (Frontiers in Sociology, 2023)
Confinement, imposed during the COVID-19 pandemic in Mexico, confronted most people with experiences of boredom. For people living with disability, however, the experience of boredom is not alien. Unfortunately, boredom and disability are topics frequently shrouded in taboo, constraining informative reflection and discussion. This perspective article briefly reflects on encounters and disagreements about these two categories in the lives of people with disabilities during the COVID-19 confinement in Mexico. The objective is to explore relevant elements for reflection and extend an invitation for critical and in-depth research on the matter.